2006
DOI: 10.1117/12.640919
|View full text |Cite
|
Sign up to set email alerts
|

Optical ordering of nanoparticles trapped by Laguerre-Gaussian laser modes

Abstract: In earlier work, it has been established that laser-induced coupling between a pair of nanoparticles can enable the generation of novel patterns, entirely determined and controlled by the frequency, intensity, and polarization of the optical input. In this paper, the detailed spatial disposition about the beam axis is determined for two-, three-and fournanoparticle systems irradiated by a Laguerre-Gaussian (LG) laser mode. The range-dependent laser-induced energy shift is identified by the employment of a quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…where f lp and A lp are standard LG beam functions as defined in [146], and α 0 is the polarizability of each spherical nanoparticle, φ is the angle between the polarization of the ABC against ψ 1 (x-axis) and ψ 2 (y-axis) for three particles in an LG beam with l = 20; lighter shading denotes higher values of E 0 ABC . Adapted from [143][144][145] input radiation and R and ψ is the azimuthal displacement angle. In the short-range region (kR 1), the leading term of equation ( 20) is determined from Taylor series expansions of sin(kR) and cos(kR).…”
Section: Structured Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…where f lp and A lp are standard LG beam functions as defined in [146], and α 0 is the polarizability of each spherical nanoparticle, φ is the angle between the polarization of the ABC against ψ 1 (x-axis) and ψ 2 (y-axis) for three particles in an LG beam with l = 20; lighter shading denotes higher values of E 0 ABC . Adapted from [143][144][145] input radiation and R and ψ is the azimuthal displacement angle. In the short-range region (kR 1), the leading term of equation ( 20) is determined from Taylor series expansions of sin(kR) and cos(kR).…”
Section: Structured Lightmentioning
confidence: 99%
“…(a) Geometry of a particle pair in a Laguerre-Gaussian beam (p = 0); (b) Clustering of nanoparticles in an LG beam; (c) Contour graphs of E 0ABC against ψ 1 (x-axis) and ψ 2 (y-axis) for three particles in an LG beam with l = 20; lighter shading denotes higher values of E 0 ABC . Adapted from[143][144][145]…”
mentioning
confidence: 99%
“…More specifically, when any particles are held at equilibrium in an optical trap or tweezers set-up, the small optically induced forces that also operate may be sufficient to produce observable departures from the behaviour expected of independent particles. In some earlier work, it has already been shown that a weak binding effect can in some cases lead to optical clustering and in others to pattern formation [42].…”
Section: Discussionmentioning
confidence: 94%